Variedades secantes e projeções lineares - Monteiro, Marisa de Sales (1997)
This work gathers together some basic results of Algebraic Geometry, such as the fiber dimension theorem (theorem 2.28), A. Terracini's lemma, (lemma 4.28) F. L. Zak theorem (Teo 4.36) in additions to necessary results in order to give the answer which, in spite of being more general, in the moment is the possible one for us to give for the question below: What should happen to the secante variety Sec(X) of a non-singular and non degenerate variety X in Ph on an algebraically closed field to guarantee the existence of a subvariety X in pn-1 isomorphic to X, where the isomorfism in particular, is a linear projection?